The Role of Biogenic Amines in Nutrition Toxicology: Review - Fatih Ozcelik; Muhammed Cihan Temel; İlbey Kayra Ozcelik and Ebru Kale (International Journal of Nutrition, 2020)
Biogenic amines, which are responsible for the realization of many physiological conditions of our body, are compounds that can be produced by microorganisms especially in fermented foods with high protein content. They can have harmful effects on human health only when taken in high amounts with food. However, in individuals with impaired anti-toxic metabolism, which is responsible for detoxification, even lower amounts may cause toxic effects. The most common health effects are nausea, vomiting, severe headaches, hypotension, hypertension, tachycardia, various allergic reactions, abdominal pain and death in more severe cases. For these reasons, legislations on biogenic amines in foods have been established with some restrictions. Food producers have been asked to comply with these legislations. However, despite all precautions, biogenic amines in foods have not been completely removed. Further research is still needed to find effective solutions to prevent biogenic amine formation. In addition, consumers need to be made aware of this issue.
Keywords: Nausea